Comparison of impact of undergraduate teaching program to assess the knowledge and attitude towards pharmacovigilance and adverse drug reporting among undergraduate medical students at a teaching medical institute in South India - Kumar, K. H. Hemanth; Akshay, J. K. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Pharmacovigilance has become an important tool to ensure the safety of patient in recent years. To ensure right practice of pharmacovigilance, proper understanding is very essential and the medical colleges with the undergraduate teaching program become a vital platform to educate and train the medical students towards pharmacovigilance. This study compares the impact of teaching program of the undergraduate curriculum in assessing the knowledge and attitude of the undergraduate medical students towards pharmacovigilance. Methods: The study includes 158 undergraduate medical students of second year being trained in pharmacology at Mysore Medical College. A validated and standardized questionnaire was distributed to all the students twice, once during their 3rd term (pre-sensitization) and the second time during their 5th term (post sensitization). Willingness to answer and complete the questionnaire was considered as consent. Results: The pre and post sensitization questionnaires were analyzed individually. A decrease from 114 to 90 students (15.19 % decrease) willing to complete the questionnaire was seen. The mean total knowledge score was 6.37±1.90 during the pre-test as compared to 6.35±1.78 in the post test analysis. An overall increase was seen with the knowledge of ADRs and pharmacovigilance. Only 18.4% knew of the presence of an ADR monitoring center in the institute pre-test which increased to 64.4% post sensitization. 81.6% answered rightly the type of ADRs that needs to be reported as compared to the 67.3% pre-sensitization. The overall attitude towards ADR reporting was seen to be in the right direction, with 71% saying that pharmacovigilance covered adequately in the curriculum. Voluntary reporting attitude increased from 74.6% to 88%. 70% of the students feel ADR reporting as a professional obligation, while only 54% felt so pre-sensitization. Conclusions: Pharmacovigilance should be included in the curriculum with more hours dedicated to teaching. Various interesting methods should be implemented to train and made aware of its importance to ensure patient safety on a global scale.